1+{2-(3-4(+[6+(7-8)+(9-10)]-11}-12
Ajutor
Răspunsuri la întrebare
Răspuns de
0
1+{2-3-4+[6+(7-8)+(9-10)]-11}-12 =
= 1+{2-3-4+[6+(-1)+(-1)] - 11} - 12 =
= 1+[2-3-4+(6 - 1 - 1)- 11] - 12 =
= 1 + ( 2- 3- 4 + 4 - 11) - 12 =
= 1 + (-12) - 12 =
= 1 - 12 - 12 =
= - 11 - 12 =
= - 23
= 1+{2-3-4+[6+(-1)+(-1)] - 11} - 12 =
= 1+[2-3-4+(6 - 1 - 1)- 11] - 12 =
= 1 + ( 2- 3- 4 + 4 - 11) - 12 =
= 1 + (-12) - 12 =
= 1 - 12 - 12 =
= - 11 - 12 =
= - 23
Alte întrebări interesante
Limba română,
8 ani în urmă
Ed. tehnologică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă